Serious games - theory and reality - Müller-Lietzkow, J.; Jacobs, S. (International Journal of Computer Science in Sport, 2012)
The following paper proposes a new two-step framework for the analysis of serious games, one that first looks at their use for personal and/or professional contexts. It then looks at the challenges serious game developers face in today`s entertainment driven environment. It suggests that societal and market challenges must be resolved to allow for the creation of serious games that can successfully compete for an audience`s attention and examine two prototype games with an appropriate mix of content and form but face several hurdles to succeed as full featured commercial products. In conclusion it suggests ways for serious games overcome these hurdles.